PERBEDAAN MOTIVASI BERPRESTASI SISWA JURUSAN MIPA DAN IPS KELAS XI SMA NEGERI 12 PEKANBARU DI MASA PANDEMI COVID-19 - Maharani, Maharani; Umari, Tri; Khadijah, Khairiyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack: This study aims to describe the differences in achievement motivation of students majoring in Mathematics and Natural Sciences and Social Sciences class XI SMA Negeri 12 Pekanbaru during the Covid-19 Pandemic. The method used in this research is quantitative with the type of comparative research. The population consists of 356 students and the number of samples taken using random sampling technique is 36 students from the Mathematics and Natural Sciences department and 36 students from the Social Sciences department. The data collection instrument used an achievement motivation questionnaire which was adapted from Djaali & Mulyono’s book and distributed via google form. Data analysis used t-test analysis. The result of the research is that the achievement motivation of students majoring in Mathematics and Natural Sciences is very high and students majoring in Social Sciences is high. From the results of the t-test analysis that has been carried out, it can be concluded that there are differences in achievement motivation between MIPA and Social studies majors during the Covid-19 Pandemic.Key Words: Achievement Motivation, Online Learning